Artificial intelligence as a policy response to teaching and learning issues in education in Ghana - Joshua Osondu; Emmanuel Jean Francois; Jesse Strycker (Journal of Global Education and Research)
This paper offers a literature synthesis on the role of artificial intelligence (AI) as a strategic policy instrument in tackling the challenges of Teaching and Learning (TL) within the Ghanaian educational context. By examining the current state and prospects of AI in education (AIEd), specifically in Ghana, this study highlights how AI can address unique educational challenges faced by Ghanaian students and educators. It adopts the dual instructor (AI and Human) model as a conceptual lens to examine how AI can revolutionize TL methodologies, thereby equipping learners for an AI-centric future. Our findings suggest that AI holds considerable promise for enhancing student engagement, personalizing learning experiences, increasing educator efficiency, and improving administrative processes. However, fully harnessing AI’s potential in education requires a strategic, contextually sensitive approach that addresses Ghana’s distinct cultural, economic, and infrastructural realities. Furthermore, integrating AIEd initiatives with overarching educational objectives is essential to maximize teaching effectiveness, student involvement, and administrative productivity. By adopting a strategic, informed, and collaborative methodology and implementing the suggested recommendations, Ghana can leverage AI to significantly upgrade its educational framework, better prepare its students for future challenges, advance its educational and developmental ambitions, and ensure AI deployment is equitable, ethical, and impactful. This study contributes to the emergent discourse on AIEd in Ghana and other similar contexts, highlighting the need for strategic policy implementations.